Cardiomyocyte-Specific Wt1 Is Involved in Cardiac Metabolism and Response to Damage. - Díaz del Moral, Sandra; Benaouicha, Maha; Villa del Campo, Cristina; Torres, Miguel; Wagner, Nicole; Wagner, Kay-Dietrich; Muñoz-Chápuli-Oriol, Ramón; Carmona-Mejías, Rita María (MDPI, 2023)
The Wilms tumor suppressor gene (Wt1) encodes a C2H2-type zinc-finger transcription factor that participates in transcriptional regulation, RNA metabolism, and protein–protein interactions. WT1 is involved in the development of several organs, including the kidneys and gonads, heart, spleen, adrenal glands, liver, diaphragm, and neuronal system. We previously provided evidence of transient WT1 expression in about 25% of cardiomyocytes of mouse embryos. Conditional deletion of Wt1 in the cardiac troponin T lineage caused abnormal cardiac development. A low expression of WT1 has also been reported in adult cardiomyocytes. Therefore, we aimed to explore its function in cardiac homeostasis and in the response to pharmacologically induced damage. Silencing of Wt1 in cultured neonatal murine cardiomyocytes provoked alterations in mitochondrial membrane potential and changes in the expression of genes related to calcium homeostasis. Ablation of WT1 in adult cardiomyocytes by crossing αMHCMerCreMer mice with homozygous WT1-floxed mice induced hypertrophy, interstitial fibrosis, altered metabolism, and mitochondrial dysfunction. In addition, conditional deletion of WT1 in adult cardiomyocytes increased doxorubicin-induced damage. These findings suggest a novel role of WT1 in myocardial physiology and protection against damage.
Keywords: Células cardiacas; Corazón - Metabolismo; Antioncogenes; Wilms’ tumor suppressor gene; Cardiomyocytes; Cardiac metabolism